1992
DOI: 10.1021/jm00081a004
|View full text |Cite
|
Sign up to set email alerts
|

2-[(2-Pyridylmethyl)sulfinyl]-1H-thieno[3,4-d]imidazoles. A novel class of gastric H+/K+-ATPase inhibitors

Abstract: 2-[(2-Pyridylmethyl)sulfinyl]thienoimidazoles were synthesized and investigated as potential inhibitors of gastric H+/K(+)-ATPase. The [3,4-d] isomers of the two possible thienoimidazole series were found to be potent inhibitors of gastric acid secretion in vitro and in vivo. Structure-activity relationships indicate that especially lipophilic alkoxy, benzyloxy, and phenoxy substituents with additional electron-demanding properties in the 4-position of the pyridine moiety combined with an unsubstituted thieno[… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
4
0

Year Published

1992
1992
2016
2016

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(4 citation statements)
references
References 4 publications
0
4
0
Order By: Relevance
“…Subsequent hydrolysis of 25 with NaOH in aqueous methanol overnight furnished 26 in excellent yield (90%). Since Omeprazole (1) and its analogues are sensitive to acidic conditions, 15 oxidation of sulfide 26 with m-CPBA was performed in DCM and aqueous NaHCO 3 solution under argon following the procedure reported by Kuhler.…”
Section: Resultsmentioning
confidence: 99%
“…Subsequent hydrolysis of 25 with NaOH in aqueous methanol overnight furnished 26 in excellent yield (90%). Since Omeprazole (1) and its analogues are sensitive to acidic conditions, 15 oxidation of sulfide 26 with m-CPBA was performed in DCM and aqueous NaHCO 3 solution under argon following the procedure reported by Kuhler.…”
Section: Resultsmentioning
confidence: 99%
“…2 Preclinical studies of thieno[2, 3-d]imidazole derivatives have shown activity in the treatment of osteoarthritis, 3 hepatitis C 4 and gastric acid regulation. 5 Figure 1 Biologically active thieno[2, 3-d]imidazoles…”
mentioning
confidence: 99%
“…However, there is another possibility of this successive reaction taking place not only within the acid compartment of the parietal cells but also at weakly acidic pH conditions outside the parietal cells . All known irreversible H + /K + -ATPase inhibitors do not exhibit activity by the mechanism described above, but they are structurally similar to the PSBs , and their analogues. On the basis of the mechanism of pH-dependent inhibition as observed in the PSBs, we aimed to find out potent and more selective inhibitors of H + /K + -ATPase in vivo, which have a different structure from PSBs.
1
…”
mentioning
confidence: 99%
“…3 All known irreversible H + / K + -ATPase inhibitors do not exhibit activity by the mechanism described above, but they are structurally similar to the PSBs 5,6 and their analogues. [7][8][9][10][11][12][13][14] On the basis of the mechanism of pH-dependent inhibition as observed in the PSBs, we aimed to find out potent and more selective inhibitors of H + /K + -ATPase in vivo, which have a different structure from PSBs.…”
mentioning
confidence: 99%